(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
The purpose of this study is to investigate how the different heel heights of women's shoes influence walking according to walking analysis findings. Identifying heel heights that do not impair walking comfort were also investigated. Ten female university students were chosen as subjects and asked to wear sample pumps with heel heights of 1.5, 3.5, 5.5, and 8.5 cm. The walking experiments focused on walking movements, muscular activities of the lower limbs, and ground reaction at the point of impact. A questionnaire was then used to determine comfort levels while walking. The analysis discovered that the height of the heel was positively correlated with vertical movement, and that the subsequent change in walking movements resulted in an increase in muscular activities and ground reaction, and a corresponding increase walking discomfort. It was also found that poor ratings were given for each measurement item when a heel height of 8.5 cm was used, leading us to conclude that comfort during walking is compromised when the heel height increases beyond 6 cm.